Do EPA administrators recommend environmental policies that citizens want? - Fredrik Carlsson; Mitesh Kataria; Elina Lampi (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
We investigate whether Swedish Environmental Protection Agency (EPA) administrator recommendations regarding improvements in environmental quality differ from citizen preferences. The scope and significance of the possible difference are assessed by conducting identical choice experiments on a random sample of Swedish citizens and a random sample of administrators working at the Swedish EPA. The experiment concerns two environmental quality objectives: a Balanced Marine Environment and Clean Air. The EPA administrators were asked to choose the alternatives they would recommend as a policy, while the citizens were asked to act as private persons. We find that the rankings of attributes differ between the two groups and that the willingness to pay (WTP) obtained from the choices made by the administrators is higher for five out of the seven attributes, and in some cases the difference between the WTPs is not only significant but also substantial. We also asked the administrators to motivate their choices in the experiment, and the main motive was ecological sustainability.
Keywords: D61; Q51; Q58; 330; Choice experiment; environmental policy; administrators; citizens; environmental objectives.; Umweltpolitik; Offenbarte Präferenzen; Test; Schweden